2021
DOI: 10.1177/0271678x211045446
|View full text |Cite
|
Sign up to set email alerts
|

Role of microcirculatory impairment in delayed cerebral ischemia and outcome after aneurysmal subarachnoid hemorrhage

Abstract: Early brain injury (EBI) is considered an important cause of morbidity and mortality after aneurysmal subarachnoid hemorrhage (aSAH). As a factor in EBI, microcirculatory dysfunction has become a focus of interest, but whether microcirculatory dysfunction is more important than angiographic vasospasm (aVS) remains unclear. Using data from 128 cases, we measured the time to peak (TTP) in several regions of interest on digital subtraction angiography. The intracerebral circulation time (iCCT) was obtained betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 81 publications
2
15
0
Order By: Relevance
“…Recently, Philipp Gölitz et al showed that the microcirculatory transit time has more advantages than the other periods of CCT 8. Thus, we used post-processing software that subdivided the different measurement points of TTP and different stages of CCT 7 18. We found that TTP VR , CCT C5-VR , and mCCT were all factors independently associated with 90-day functional independence.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, Philipp Gölitz et al showed that the microcirculatory transit time has more advantages than the other periods of CCT 8. Thus, we used post-processing software that subdivided the different measurement points of TTP and different stages of CCT 7 18. We found that TTP VR , CCT C5-VR , and mCCT were all factors independently associated with 90-day functional independence.…”
Section: Discussionmentioning
confidence: 89%
“…18 The regions of interest (ROIs) were placed in the intravenous vertical portion of the internal carotid artery (ROI C5 ), the cortical segment of the rolandic artery (ROI M4 ), and the rolandic vein (ROI VR ) to calculate the time-density profile. 7 The time to peak (TTP) on the time-density curve for each region of interest was recorded as TTP C5 , TTP M4 , and TTP VR . CCT is defined as the difference in the time to peak intensity between ROIs.…”
Section: Cerebral Circulation Time Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…During aneurysm clipping surgery, Uhl et al observed monosegmental and pearl-string multisegmental microvasospasms in arterioles for the first time, with a 75% reduction in cortical microcirculation after SAH. 12 A recent digital subtraction angiography (DSA) study found that the intracerebral circulation time within 24 hrs after ictus was significantly correlated with the occurrence of delayed cerebral ischaemia in SAH patients as an independent factor in addition to angiographic vasospasm in traditional understanding, 13 which suggests that microcirculatory dysfunction in the ultra-early and subacute phases can be a causative factor for delayed cerebral ischaemia development and poor outcome.…”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 99%
“…Cerebral vasospasm after aneurysmal SAH (aSAH) is defined as large and medium intracranial artery stenosis. Cerebral vasospasm can lead to local cerebral hypoperfusion and DCI and is one of the major causes of death and disability in patients with aSAH 106 . The exact mechanism of vasospasm after SAH is not fully understood, but many mechanisms have been proposed, such as endothelial injury and microthrombi formation; smooth muscle contraction, resulting from the lysis of subarachnoid blood clots and blood degradation products and hemoglobin released into the subarachnoid space; decreased NO production leading to prolonged vasoconstriction; increased production and release of the potent vasoconstrictor endothelin‐1; cortical spreading depolarization; inflammation‐mediated oxidative stress and free radical damage to smooth muscle cells; and upregulation of apoptotic pathways 12,107 …”
Section: Protective Effects and Underlying Mechanisms Of H2s In Sahmentioning
confidence: 99%